Listening, Thinking, Being : Toward an Ethics of Attunement - Lipari, Lisbeth, 1960- (Book collections on Project MUSE., 2014)
"Explores listening as a fundamental human endowment connected with language and thought, and its potential for social, personal, and political action. Incorporates historical, literary, intercultural, scientific, musical, and philosophical perspectives"--Provided by publisher.